Comparative performance analysis between winners and losers in freestyle wrestling at the 2023 World Championship - Georgiy Korobeynikov; Wojciech Cynarski; David Curby; Milorad Dokmanac; Yrui Tropin; Mykola Latyshev; Rashid Matkarimov; Fikrat Kerimov; Lesia Korobeinikova; Shukurjon Gaziyev (Здоров’я, спорт, реабілітація)
Background and purpose